In vivo Investigation of the Therapeutic Potential of Ziziphus mauritiana Against Inflammatory Bowel Disease in Albino Wistar Rats - Sunidhi Dave; Pravin Tirgar; Tushar Undhad; Keval Raval (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Purpose: To examine the potential anti-inflammatory activity of the methanolic extract of Ziziphus mauritiana (MEZM) in inflammatory bowel disease conditions. Materials and Methods: A total of 36 adult male Albino Wistar rats were divided into six groups. The first group (normal control) was administered with normal saline, and the second group (disease control) was administered with 4% acetic acid via the rectal route. The third group (sulfasalazine group) received the standard treatment of 100 mg/kg sulfasalazine, while three test groups were administered with 100, 200, and 300 mg/kg of MEZM. On the 14th day, a macroscopic examination was conducted to assess colonic inflammation, ulceration, and levels of cytokines including interleukin-4 (IL-4), interleukin-6 (IL-6), interleukin13 (IL-13), and tumour necrosis factorα (TNFα), which were estimated to investigate the inflammatory response. Result: The cytokine levels increased significantly in the disease control group compared to the normal control group with P value <0.0001. Treatment with sulfasalazine (100 mg/kg) and different doses of MEZM significantly reduced the levels of IL-4 and IL6 compared to the disease control group with P value <0.0001. Animals treated with MEZM (100 mg/kg) showed significant reduction in IL-13 and TNF-α levels with P value <0.001. Levels of IL-13 and TNF-α levels were significantly reduced in animals treated with sulfasalazine (100 mg/kg) and MEZM (200 and 300 mg/kg) with P value <0.0001. Conclusion: The study indicates that MEZM may exert potential anti-inflammatory action in IBD conditions.